THE REALIZATION OF POLITENESS STRATEGIES IN ENGLISH DIRECTIVES AMONG MEMBERS OF PALEMBANGNESE ETHNIC GROUPS IN PALEMBANG, SOUTH SUMATRA, INDONESIA: TEACHING JOURNEY - Afriani, Susi Herti (Istinbath, 2015)
The purpose of this study is to describe the realization of politeness strategies in the English Directives Among Members of Palembangnese ethnic groups in South Sumatra, Indonesia: Teaching Journeys.This study also aims to examine the relationship between the realization of face threatening Acts among the Palembangnese and culture with their style in delivering speech acts. This study is a qualitative and quntitative research with pragmatics and sociolinguistics approach. Pragmatics used to analyze how they affect speech and the interlocutors in communication. This research may show reflection of cultural values. Language is closely related to culture. Disclosure cultural values can be done correctly by using the language in question. Language is used as a means of communication, and communication is one of the functions to maintain social relationships. In short, the research data will be captured by using a questionnaire survey, which triangulated with interviews with several sources plus regular observation. In conclusion, teaching English need to understand a concept of politeness strategies, because every culture is unique. Therefore, clearly, the researcher looked at the problem as follows: the politeness strategy tells what used among members of ethnic groups in Palembang , and what strategies are most likely to occur, and what is represented (implicatures) will be answered in this research.